Intellectual cooperation at the League of Nations: shaping cultural and political relations - Grandjean, Martin; Laqua, Daniel (Historical Series, 2025)
The construction of a new global order after the First World War required not only political and economic efforts, but also the coordination of scientific and cultural relations on an international scale. To this end, the League of Nations launched a range of initiatives, including the creation of its International Committee on Intellectual Cooperation (1922), the foundation of the Paris-based International Institute of Intellectual Cooperation (1925-26) as well as the formation of various auxiliary bodies. These ventures aimed to develop a collaborative dynamic around issues as diverse as scientific cooperation, educational means for peace as well as artistic and literary relations. Attracting some of the era’s most eminent intellectuals, these initiatives did not lead to the creation of a “League of Minds”, as some of the architects of the League of Nations had so eagerly hoped. However, as this volume demonstrates, these efforts did play a key role in the development of cultural diplomacy and in the evolution of transnational fields of action during the interwar period. Moreover, the history of transnational intellectual cooperation in this period illuminates wider issues surrounding international relations and the development of international organizations.